Serum autoantibody profiles in cancer patients treated with immune checkpoint inhibitors: a cross-sectional study - Chen, Kun; Guo, Bao’e; Liu, Rufeng; Wang, Juan; Zhang, Chen; Xu, Guobing (Frontiers in Oncology, 2025)
BackgroundThe relationship between autoantibody profiles and immune checkpoint inhibitor (ICI) therapy in cancer patients remains incompletely characterized. This cross-sectional study investigated serum autoantibody (AAb) prevalence and profiles across multiple tumor types before and after ICI therapy.MethodsThis study analyzed serum autoantibodies in 808 participants: 358 treatment-naïve cancer patients (ICI- group), 250 cancer patients following ≥6 months of ICI therapy (ICI+ group), and 200 healthy controls (HC). The cancer cohort comprised 10 solid tumor types. Serum samples were analyzed for antinuclear antibodies (ANA), antiphospholipid antibodies (aPL), anti-neutrophil cytoplasmic antibodies (ANCA), and anti-thyroid antibodies (ATA) using automated quantitative immunoassays.ResultsCancer patients demonstrated significantly elevated AAb prevalence compared to healthy controls. The ICI− group showed positivity rates of 20.1% for ANA, 11.5% for aPL, 1.7% for ANCA, and 17.3% for ATA, compared to 10.5%, 4.5%, 1.5%, and 9.5% in healthy controls, respectively. After ICI therapy, ANA positivity increased to 33.6%. CTLA-4 inhibitor recipients demonstrated higher ANA frequencies than PD-1/PD-L1 monotherapy recipients (57.1% vs 27.1%),. Tumor stage did not significantly influence AAb prevalence. Colorectal, hepatocellular, and renal cancers showed significant ANA increases after ICI treatment. Anti-Scl-70, anti-SSA-60, and anti-RNP were the most frequently elevated ANA subtypes. Anti-thyroglobulin was the most responsive ATA subtype following ICI therapy.ConclusionsANA profiles vary across tumor types and differ between treatment-naïve and ICI-treated patients. CTLA-4-treated patients exhibit higher ANA frequency. Different tumors exhibit distinct preferences for AAb expression patterns. Serum AAb profiling may serve as a valuable tool for immunotherapy monitoring and risk stratification for immune-related adverse events.